The Art as the Conjectured Possible. - Bulatov, Dmitry (Russian Studies in Philosophy, 2019)
The fact that modern artists are turning toward science and the latest technologies—robotics, information technology, biomedicine—forces us to reformulate our concept of art. One need only imagine a "semi-living" cybernetic organism or a neural culture in the halls of a museum or gallery to understand that the existing art infrastructure (storage, representation, etc.) is entirely unequipped for these kinds of works. All these nonhuman subjects interacting with one another give rise to a complex systemic whole, new spaces for the existence of art, where man is no longer assigned the most important role. Are there working concepts and formats of art that fall within the framework of these technological innovations? Can they help stimulate new, critical art research and interventions at the intersection of art, science, and technology?